Trp-Containing Antibacterial Peptides Impair Quorum Sensing and Biofilm Development in Multidrug-Resistant Pseudomonas aeruginosa and Exhibit Synergistic Effects With Antibiotics - Shang, Dejing; Han, Xue; Du, Wanying; Kou, Zhiru; Jiang, Fengquan (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa uses quorum sensing (QS) to control virulence, biofilm formation and antibiotic efflux pump expression. The development of effective small molecules targeting the QS system and biofilm formation represents a novel attractive strategy. In this present study, the effects of a series of Trp-containing peptides on the QS-regulated virulence and biofilm development of multidrug-resistant P. aeruginosa, as well as their synergistic antibacterial activity with three classes of traditional chemical antibiotics were investigated. The results showed that Trp-containing peptides at low concentrations reduced the production of QS-regulated virulence factors by downregulating the gene expression of both the las and rhl systems in the strain MRPA0108. Biofilm formation was inhibited in a concentration-dependent manner, which was associated with extracellular polysaccharide production inhibition by downregulating pelA, algD, and pslA transcription. These changes correlated with alterations in the extracellular production of pseudomonal virulence factors and swarming motility. In addition, the combination of Trp-containing peptides at low concentration with the antibiotics ceftazidime and piperacillin provided synergistic effects. Notably, L11W and L12W showed the highest synergy with ceftazidime and piperacillin. A mechanistic study demonstrated that the Trp-containing peptides, especially L12W, significantly decreased β-lactamase activity and expression of efflux pump genes OprM, MexX, and MexA, resulting in a reduction in antibiotic efflux from MRPA0108 cells and thus increasing the antibacterial activity of these antibiotics against MRPA0108.